Comparing two different presentations of Takayasu arteritis - S. A. F. Kurukulasuriya; D. Munidasa (Sri Lanka College of Internal Medicine, 2024)
Reported here are two Asian patients with Takayasu arteritis (TA) with contrasting presentations and responses to treatment. The first patient was a 53-year-old man who presented with disabling abdominal pain. Imaging revealed thickening of the coeliac axis extending to common hepatic and splenic arteries causing external compression with luminal narrowing. There was uniform thickening of the aortic arch and the wall of the descending aorta along with retroperitoneal fibrosis. Early treatment resulted in almost complete remission in eight weeks. The second patient was a 48-year-old woman with pain down the left upper limb with eventual ischaemia of the fourth finger. Imaging revealed circumferential wall thickening at the origin of the left subclavian artery. Treatment started after 3 weeks of the initial presentation, and took up to 14 months for clinical improvement. The relative rarity of this disease and the heterogeneous nature of its clinical manifestations predispose to late diagnosis and delayed treatment. Clinical suspicion and relevant imaging are crucial for the early and accurate diagnosis and management of patients with TA.